Connecting and dissecting galaxies' angular momenta and neutral gas in a hierarchical universe: cue Dark Sage. Issue 4 (1st October 2018) - Stevens, Adam R H; Lagos, Claudia del P; Obreschkow, Danail; Sinha, Manodeep
Abstract: We explore the connection between the atomic gas fraction, f atm, and 'global disc stability' parameter, q, of galaxies within a fully cosmological context by examining galaxies in the Dark Sage  semi-analytic model. The q parameter is determined by the ratio of disc specific angular momentum to mass, i.e.  q  ∝  j disc / m disc . Dark Sage  is well suited to our study, as it includes the numerical evolution of one-dimensional disc structure, making both j disc and q predicted quantities. We show that Dark Sage  produces a clear correlation between gas fraction and j disc at fixed disc mass, in line with recent results from observations and hydrodynamic simulations. This translates to a tight q – f atm sequence for star-forming central galaxies, which closely tracks the analytic prediction of Obreschkow et al. The scatter in this sequence is driven by the probability distribution function of mass as a function of j (PDF of j ) within discs, specifically where it peaks. We find that halo mass is primarily responsible for the peak location of the PDF of j, at least for low values of q . Two main mechanisms of equal significance are then identified for disconnecting f atm from q . Mergers in the model can trigger quasar winds, with the potential to blow out most of the gas disc, while leaving the stellar disc relatively unharmed. Ram-pressure stripping of satellite galaxies has a similar effect, where f atm can drop drastically with only a minimal effect to q . We highlight challenges associated with following these predictions up with observations.